Energy And Environment - Environmental Protection - Farkhod Muhammadievich Alqarov, (International Scientific and Current Research Conferences, 2021)
Energy, electricity, power plants, environmental impact, thermal energy. Within all sectors of the economy, such as oil, gas, coal, and nuclear energy, energy has a major impact on the environment. He grew at an incredible rate, and his strength increased. The growing demand for electricity can now be met in a variety of ways: a sharp increase in coal, oil and gas production, or the rational and integrated use of extracted resources.